Safeguarding Minors' Personal Data: Legal Principles in Information Security in Ukraine and Eurupean - Kobko, Yevhen; Foros , Hanna; Shperun, Khrystyna; Nikitinskyi, Oleksandr; Savchuk, Roman (Syariah: Jurnal Hukum dan Pemikiran, 2023)
The research aims to uncover the legal regulations pertaining to the protection of minors' personal data, considered a crucial component of informational security. Through an analysis of Ukrainian and European legislation, in conjunction with the General Data Protection Regulation and the California Consumer Privacy Act, this study seeks to explore preventive measures against third-party abuse of children's information. The research highlights the responsibilities imposed on state authorities and legal entities, based on Ukrainian and European legislation, to safeguard personal data. The methodology employed in this article involves the utilization of both general scientific and specialized methods of scientific cognition. The specificity of the research subject, along with its purpose and tasks, guided the selection of these methods. The research results reveal various problematic issues related to the collection, storage, use, and distribution of personal data of minors. The obligation to protect an individual's rights to the processing and preservation of personal data or private information is a responsibility placed on state authorities in accordance with the legislation of Ukraine and European countries (Germany, Switzerland, France, Italy, Norway, Great Britain), as well as on legal entities that own or store the specified personal data. In conclusion, the protection of personal data emerges as a fundamental right, integral to the broader rights of family and private life. The study also underscores the importance of international cooperation mechanisms in addressing this multifaceted issue.